Batwing incision for a case of bilateral fungal zygomatic osteomyelitis. Issue 5 (31st May 2022) - Yadav, Sanjeev; Saini, Ashish; Singh, Abhimanyu; Verma, Hitesh
Abstract : Zygomatic osteomyelitis is a rare occurrence due to rich collateral blood supply of bone. A man in his 30s presented with complaints of pain over bilateral cheek and pus discharge below the eye on lateral aspect. He was a known case of COVID-19 associated mucormycosis postendoscopic debridement of sinuses 3 months back. Radiology revealed bilateral destruction of zygoma with discharging sinus. Microbiological analysis confirmed aseptate hyphae in pus, and a diagnosis of bilateral fungal zygomatic osteomyelitis made. Under general anaesthesia, sequestrectomy done using bilateral lateral rhinotomy with extended Dieffenbach's approach (batwing incision). Postsurgery 3000 mg of liposomal amphotericin was administered. There was no enophthalmos or restricted eye movements postoperatively. Follow-up MRI suggested minimal inflammatory enhancement in maxillary sinus. Patient was discharged on oral antifungals.